1OTrastuzumab emtansine (T-DM1) vs trastuzumab (H) in Chinese patients (pts) with residual invasive disease after neoadjuvant chemotherapy for HER2-positive breast cancer (BC) in the phase III KATHERINE study. (24th November 2019) - Huang, C; Yang, Y; Kwong, A; Chen, S-C; Tseng, L-M; Liu, M-C; Shen, K; Wang, S; Ng, T-Y; Feng, Y; Sun, G; Yan, I R; et al.
Abstract: Background: Pts with HER2+ early BC and residual invasive disease after neoadjuvant chemotherapy plus HER2-targeted therapy have a higher risk of recurrence and death than those with a pCR. The KATHERINE (NCT01772472) study showed significantly improved invasive disease-free survival (IDFS) with adjuvant T-DM1 vs H in this population. Here, we compare Chinese pts in KATHERINE to the overall population. Methods: Pts with HER2+ BC and residual invasive disease after taxane- and H-containing neoadjuvant chemotherapy followed by surgery were randomized 1:1 to 14 cycles of adjuvant T-DM1 (3.6 mg/kg IV q3w) or H (6 mg/kg IV q3w). IDFS and the secondary endpoints of disease-free survival including non-invasive breast cancers, overall survival, distant recurrence-free interval, and safety were compared between Chinese pts (mainland China, Taiwan, Hong Kong) and the overall population. Results: There were 101 (6.8%) Chinese pts in KATHERINE. IDFS was greater in the T-DM1 vs the H group (HR = 0.57; 95% CI: 0.25–1.31), with similar results for secondary endpoints (Table). As in the overall population, Chinese pts receiving T-DM1 vs H had more grade ≥3 adverse events (AEs; 39% vs 4%), serious AEs (SAEs; 20% vs 2%); and AEs leading to treatment discontinuation (28% vs 0). The most common grade ≥3 AE in the T-DM1 arm was thrombocytopenia (22%), a frequency higher than in the overall population (6%). Grade ≥3 hemorrhage was reported in 1 pt (T-DM1 arm). All grade ≥3 thrombocytopenia was resolved or resolving at data cutoff. Conclusions: Consistent with the overall study population, T-DM1 was associated with increased efficacy compared to H in Chinese pts. Compared to all pts, increases in SAEs, grade ≥3 AEs, and AEs leading to discontinuation were observed in Chinese pts and were driven by an increase in thrombocytopenia, consistent with previous data in Asian pts. Clinical trial identification: NCT01772472. Editorial acknowledgement: Medical writing assistance was provided by Twist Medical and was funded by F. Hoffmann–La Roche. Legal entity responsible for the study: F. Hoffmann-La Roche. Funding: F. Hoffmann-La Roche. Disclosure: C. Huang: Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Amgen; Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): EirGenix; Research grant / Funding (institution): MSD; Research grant / Funding (institution): OBI Pharma. Y. Yang: Research grant / Funding (institution): Roche; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Ono; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): Celgene; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Mundipharma; Research grant / Funding (institution): Orient Europharma; Full / Part-time employment: Taichung Veterans General Hospital. A. Kwong: Honoraria (self), ICG Fluorescence in Breast Surgery speaker: Stryker; Honoraria (self), Chairing Meeting: AstraZeneca; Honoraria (self), Chairing Meeting: Pfizer; Honoraria (self), Honoraria (institution), Chairing Meeting, Support on trial to HKU: Roche; Honoraria (institution), Suppprt on trial to HKU: Merck; Honoraria (institution), Support on trial to HKU: Novartis; Honoraria (institution), Supporting device & consumables for Prospective Study on Cryosurgery for treatment of Early Breast Cancer.: WKK Medical Equipment company limited; Leadership role, Chairman: Hong Kong Hereditary Breast Cancer Family Registry; Leadership role, Founding member: Asian BRCA (ABRCA); Leadership role, Council Member: Hong Kong Society of Breast Surgeons. L-M. Tseng: Advisory / Consultancy, Travel / Accommodation / Expenses: Amgen; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: AstraZeneca. M-C. Liu: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Roche. Y. Feng: Full / Part-time employment: Roche (China) Holding Ltd. G. Sun: Full / Part-time employment: Roche (China) Holding Ltd. I.R. Yan: Full / Part-time employment: Roche (China) Holding Ltd. All other authors have declared no conflicts of interest.